Apical versus septal pacing - can we chose the localization of ventricular lead in order to prevent upgrade to cardiac resynchronization therapy?. (19th May 2022) - Silverio Antonio, P; Couto Pereira, S; Brito, J; Valente Silva, B; Alves Da Silva, P; Garcia, B; Simoes Oliveira, C; Nunes-Ferreira, A; Magalhaes, A; Bernardes, A; Lima Da Silva, G; Carpinteiro, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Right ventricular apical pacing (RVAp) may be deleterious to ventricular function and hemodynamics due to pacing induced dyssynchrony. In the last decades, some studies showed that RVAp has been associated with heart failure, deterioration of left ventricular function and high mortality. Some patients (pts) may need, during the follow up (FUP), an upgrade to cardiac resynchronizaon therapy (CRT). New techniques have emerged such as RV lead implantation in the high septum or outflow RV tract (RVOT) and, more recently, His bundle/LB pacing. Purpose: To compare the need for upgrade to CRT in patients with RVAp versus septal/RVOT pacing. Methods: Retrospective single-center study of consecutive pts that implanted pacemakers in a tertiary center between January 1995 and December 2020. We collected data regarding pacing indication, RV pacing site (apex versus septum/RVOT) and need for an upgrade to CRT during follow up (FUP). Our primary endpoint was upgrade to CRT during the FU period. In the model, the impact of localization of the implanted lead on the survival free from upgrade was estimated assuming a neutral effect on mortality. Statistical analysis was performed using T-student test and logistic regression. Results: We included 8761 pts, 60.2% (n=5275) were male, with a mean age of 76.5±10.7 years. The main indications for pacemaker implantation were (1) complete atrioventricular (AV) block (2239, 25.6%), (2) sick sinus syndrome (2211, 25.2%), (3) atrial fibrillation with AV block or bradycardia with significant pauses (17.4%) and (4) Mobitz II 2nd degree AV block (1467, 16.7%). RVAp was performed in 1746 (20%) patients and RVOT/septal pacing in 6933 patients (80%; RVOT in 657 (9, 5%)). During FUP, 26 (1, 5%) RVAp pts and 52 (0, 8%) RVOT/septal pacing pts underwent upgrade to CRT, in a total of 78 pts (CRT-P in 54 patients and CRT-D in 24 patients). We observed that patients with RVAp had twice the risk of CRT upgrade during FUP (OR: 2, 0 (IC 95% 1, 25-3, 21), p=0, 004) when compared to patients with RVOT/septal pacing. Conclusions: Patients with RVAp presented a 2-fold higher risk for upgrade to CRT when compared to patients with RVOT/septal pacing in our center. This retrospective analysis shows that lead implantation in the septum/RVOT should be preferred instead of the apex to reduce pacing induced dyssynchrony and need for CRT upgrade.